The Differences of Condom use Among Transgender to Regular Partner and Clients - Septiana Ningtiyas; Prijono Satyabakti (Universitas Airlangga, 2016)
The prevalence of Human Immunodeficiency Virus (HIV) in transgender female in Surabaya based on the 2011 Integrated Biological and Behavioral Survey (IBBS) has reached 24%. The high prevalence in the transgender female group is due to inconsistent risky sexual behavior in using condoms and changing sexual partners. The transgender female 's condom use program hasn't reached the target. The purpose of this study is to describe the differences in the use of condoms in transgender female with regular partners and customers. This research is a qualitative descriptive study with a cross-sectional study design. The informants of this study were 9 people who were taken by purposive sampling with the criteria of transgender female sex workers who list on the Surabaya City Transgender Association (Perwakos), still actively peddling sex, having permanent partners or having had permanent partners, sexual activity in Surabaya. The variables studied were knowledge, attitude, perception, condom use. Data analysis techniques using data transcripts, data reduction, data presentation, and verification. The results showed condom use in couples remained lower than customers. This is caused by attitude, bad perception, accompanied by the dominance of emotional factors. There are no differences in condom use between regular partners and customers. Therefore, Perwakos needs to motivate transgender female to always use condoms when having sex with regular partners and customers, as well as increased knowledge about HIV-Acquired Immunodeficiency Syndrome (AIDS) and the benefits of condoms to permanent partners and transgender female customers.